Imposition of quota and the ability of the developer to sell housing units allocated for Bumiputera in Malacca / Irdha Hakim - Hakim, Irdha (Faculty of Business and Management, 2006)
In Malacca, any developers who wanted to develop a residential areas or housing estates must allocate quotas for Bumiputera and Non-Bumiputera quota. To assist the developers to sell the allocated units, The Government has developed a subsidiaries "PERTAM Properties Sdn Bhd (PPSB)" to manage and guide the developers in the disposal of such quota. Despite of the helps given by PERTAM, majority of the quota allocated for Bumiputera cannot be sold by the developers. Thus this study is undertaken to examine what are the pertinent factors that lead to the existing problem. The data for this study is sourced from questionnaires administrated used personal interviews on 50 selected developers (98% response rate). A set of questionnaires is designed using 68 items - instruments. The 68 items were analyzed. Four factors grouped into status of property, site selection, price, and material selection used and tested for its reliability and produced an alpha Cronbach value of 0.782. The findings conclude that the four factors analyzed in this study do not have a significant relationship with the selling performance as every P value for each factors resulted P > 0.05 which; P = 0.084 > 0.05 before CF and P == 0.209 > 0.05 after CF for the status of property, P = 0.005 < 0.05 before CF and P = 0.814 > 0.05 after CF for site selection, P = 0.376 > 0.05 before CF and P = 0.665 > 0.05 after CF for price and for matelials selection the P value before CF is P == 0.440 > 0.05 and P = 0.885 > 0.05 after CF. It is found that the quota allocated cannot be sold mainly because the Bumiputera prefers to buy units which have the Certificate of Fitness (CF) as being tested that the selling performance before CF is highly significant with the selling performance after CF as the t value of 7.773 with P value of 0.000.